Existence and features of the myodural bridge in Gentoo penguins: A morphological study. - Cheng Chen; Sheng-Bo Yu; Yan-Yan Chi; Guang-Yuan Tan; Bao-Cheng Yan; Nan Zheng; Hong-Jin Sui (PLoS ONE)
Recent studies have evidenced that the anatomical structure now known as the myodural bridge (MDB) connects the suboccipital musculature to the cervical spinal dura mater (SDM). In humans, the MDB passes through both the posterior atlanto-occipital and the posterior atlanto-axial interspaces. The existence of the MDB in various mammals, including flying birds (Rock pigeons and Gallus domesticus) has been previously validated. Gentoo penguins are marine birds, able to make 450 dives per day, reaching depths of up to 660 feet. While foraging, this penguin is able to reach speeds of up to 22 miles per hour. Gentoo penguins are also the world's fastest diving birds. The present study was therefore carried out to investigate the existence and characteristics of the MDB in Gentoo penguin (Pygoscelis papua), a non-flying, marine bird that can dive. For this study, six Gentoo penguin specimens were dissected to observe the existence and composition of their MDB. Histological staining was also performed to analyze the anatomic relationships and characteristic of the MDB in the Gentoo penguin. In this study, it was found that the suboccipital musculature in the Gentoo penguin consists of the rectus capitis dorsalis minor (RCDmi) muscle and rectus capitis dorsalis major (RCDma) muscle. Dense connective tissue fibers were observed connecting these two suboccipital muscles to the spinal dura mater (SDM). This dense connective tissue bridge consists of primarily type I collagen fibers. Thus, this penguin's MDB appears to be analogous to the MDB previously observed in humans. The present study evidences that the MDB not only exists in penguins but it also has unique features that distinguishes it from that of flying birds. Thus, this study advances the understanding of the morphological characteristics of the MDB in flightless, marine birds.